Refractory/Relapsed High-Grade B-Cell Lymphoma in the Elderly: A Special Therapeutic Challenge - Sretenović, Snežana (Open Access Macedonian Journal of Medical Sciences, 2023)
BACKGROUND: According to the 2016 World Health Organization classification of lymphoid neoplasms, high- grade B-cell lymphoma (HGBL) is defined as a new category for aggressive diffuse large B-cell lymphomas (DLBCL), including DLBCL NOS as well. CASE REPORT: An 80-year-old patient was admitted because of an enlargement of the lymph node located in the right neck region. The patient underwent 6 cycles of R-CHOP, which is considered to be the standard treatment for non-Hodgkin lymphomas (NHL) DLBCL (NOS) CSII B “Bulky,” and he subsequently achieved complete remission (CR). A lymph node biopsy was performed, PH No. 12742/21, which revealed the following: LCA+, CD79 α CD20+, and CD5+, in approximately 50% of the cells, NHL DLBCL (NOS) was of GCB origin, etc. The international prognostic index risk score was 2, the cumulative illness rating scale score was 4. In addition, no bone marrow infiltration was reported. A COP-based chemotherapy protocol was administered, after which the evaluation showed disease relapse. Multi-slice spiral computed tomography (MSCT) follow-up showed an enlarged conglomerate of lymph nodes in all the neck levels. Dg: NHL DLBCL (NOS) CS IVB “Bulky” E (the hypopharynx). The echocardiography results were the following: (EF 50%, aortic insufficiency with MR1+, TR1+ of the aortic valve 3+). The patient was presented to the Consilium, who decided to apply the following therapy (Polatuzumab vedotin + Rituximab + Bendamustine). After III cycle of treatment, MSCT follow-up was performed. The patient gained weight, oral food intake was enabled, whereas the quality of life was significantly improved. CONCLUSION: The administration of ta treatment may be provided to elderly patients with relapsed HGBL.